PEMANFAATAN SOFTWARE GEOGEBRA PADA MATAKULIAH MATEMATIKA UNTUK MENINGKATKAN KEMANDIRIAN BELAJAR MAHASISWA PRODI ARSITEKTUR UNIVERSITAS MALIKUSSALEH - Eri Saputra; Samsul Bahri; Effan Fahrizal (Program Studi Pendidikan Matematika, STKIP Bina Bangsa Getsempena, 2019)
The development of the education world towards ICT (Information and Communication Technology) in this era made education more modern. More software or software is available free of charge that can be used for teaching and learning processes especially mathematics courses. Geogebra software is one of the software that can help students to learn independently in learning mathematics. This is because